Factors affecting the adoption of business intelligence solutions in a public sector organisation - Tshehla, Modiketse (University of the Witwatersrand, Johannesburg, 2023)
Business Intelligence Solutions (BIS) continue to play a significant role in organisations and businesses in today’s information age. The adoption of BIS enables an organisation to gain a competitive advantage, generate accurate and faster data reporting, improve customer service, and increase revenue. The benefits of BIS have been realised in private sector organisations. However, the South African public sector is yet to release the benefits of adopting business intelligence solutions. The factors that affect the adoption of business intelligence solutions in a South African public sector organisation have not been fully investigated. This study explores factors that division managers perceive to be salient in influencing the adoption of a visualisation and data exploration BIS available in a public sector organisation in South Africa. The study was underpinned by Tomatzky and Fleischer’s Technology Organisation Environment (TOE) framework which was applied previously in the adoption of information system (IS) at the organisation level.The framework provided the lens from which adoption was studied by considering influences from the technological context, the organisational context and the environmental context. The following main research question guiding the study was addressed: What aspects of the visualisation and data exploration BIS are perceived to influence the adoption of the BIS in the public sector organisation. The organisation in the study provides training and development to public sector employees of the South African government. The study interviewed 10 senior managers with at least three years’ experience in the organisation. It was found that expected benefits from the technology and its compatibility are important for the adoption of BIS. Within the public sector organisation studied, stakeholder engagement; organisational culture; and available financial resources were also found to be important and supported by the literature. While service provider support was found to be crucial in the BIS adoption from the environmental context, the size of the organisation and the government regulations were found not to be influential in the adoption of BIS in a public sector organisation. The stimulation of employee interest and the importance of data quality were discovered to be the most important reasons the BIS was adopted. This research contributed to the improvement of theory by extending IS literature on BIS adoption and by testing the TOE theoretical framework in the South African public sector context. This study adds to the body of knowledge by extending the use of the TOE framework as a suitable tool for the study of BIS adoption. Furthermore, the study contributed by uncovering factors that influence the adoption of BIS in the South African public sector context. The results may help the South African and other countries’ public sector organisations to become more aware of the factors that influence the adoption of BIS. Practitioners and managers could be better prepared and minimise the BIS adoption risks by considering these factors
A research report submitted in partial fulfillment of the requirements for the degree of Master of Commerce to the Faculty of Commerce, Law and Management, School of Business Science,Department of Information Systems, University of the Witwatersrand, Johannesburg, 2023
Keywords: Business Intelligence adoption; Public sector; Stakeholder engagement; Government regulations; Organisational culture; South Africa; UCTD; SDG-8: Decent work and economic growth